Mentoring for skills development among cataloguers - Bello, Musa Ayinla (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2012)
Academic libraries as major components of higher education provide significant support to institutional goals. Many of the library services in this digital age have tended towards users self-exploration of the resources unaided. With the geometrical growth in information resources, cataloguers' task of bibliographic control for efficient and timely access has become more challenging. However, the cataloguers' skills, knowledge and strength continue to dwindle. This has generated concern for the profession worldwide in the recent time. In addition, there has been a shift in educational training and consequently decrease in skills development and proficiency of cataloguers. In Nigeria, unsatisfactory learning environment, training infrastructure and lukewarm attitude to cataloguing course by educators and students have aggravated the problem. Consequently, the cataloguers are lacking sufficient professional skills needed to perform their duties. This in turn affects academic library services provision. Therefore, this study investigates cataloguers' perceptions on mentoring for skills development and critical role of mentoring for proficient skills development across university libraries in Nigeria. The main objectives of the study are to investigate cataloguers' perception on mentoring and use of mentoring in knowledge transfer for skills development and examine the relationship between demographic factors of cataloguers and their perceptions on mentoring for skills development. The study addresses questions on (1) the state of mentoring in Nigerian libraries, (2) the perception of cataloguers on mentoring for development, (3) perception of cataloguers on knowledge transfer through mentoring for cataloguing, managerial and research skills development, and examine whether there are relationships between demographic factors of cataloguers and their perceptions on mentoring for skills development. Findings indicated there were informal mentoring programmes in libraries and assessed to be satisfactory and invaluable. The majority of the respondents perceived mentoring enhanced cataloguers' development, that knowledge transferred through mentoring brought about cataloguing, managerial and research skills improvement and enhanced their expertise, proficiency and productivity. There were relationships between the cataloguers' demographic factors with skills development and knowledge transfer through mentoring. The associations showed moderate to strong relationships at lower age, lesser experience and at lower levels of education. Gender showed strong relationships with the variables, but there was no inter-gender difference among the respondents. The result of the study indicated that use of mentoring help cataloguers apply their learning and develop mastery of subject. Thus, library management needs to support mentoring as it develops talents, abilities and attributes through knowledge sharing and transfer that enhance skills development.